Intraperitoneal splenosis mimics peritoneal carcinomatosis of leiomyosarcoma and ovarian cancer - Yu-Chien Lin; Chi-Chun Liao; Hung-Cheng Lai (Elsevier, 2020)
Objective: Leiomyosarcoma and ovarian cancer are often diagnosed late due to the absence of initial symptoms. Patients seek help when abdominal distension occurs; this is associated with pelvic tumor and carcinomatosis. Initial imaging often reveals pelvic tumors with diffuse abdominal nodules; however, this imaging could be misleading, such as in the cases of splenosis. Case report: A female presented with vaginal bleeding at our outpatient department. Serum CA125 level was elevated. Abdominal and pelvic CT showed multiple uterine masses and left adnexal cysts with peritoneal nodules. Leiomyosarcoma or ovarian cancer with carcinomatosis was suspected. Exploratory laparotomy was performed. Multiple purple spots spreading over peritoneal cavity were noted during the surgery. Pathological examination revealed adenomyosis with multiple uterine myomas and left ovarian endometrioma. Splenic tissues peritoneal implants were observed. Conclusion: In patients with a history of spleen rupture or splenectomy, splenosis should be considered in the differential diagnosis, especially in young patients.